Protein Folding Protocols
DOI: 10.1385/1-59745-189-4:251
|View full text |Cite
|
Sign up to set email alerts
|

Packing Regularities in Biological Structures Relate to Their Dynamics

Abstract: The high packing density inside proteins leads to certain geometric regularities and also is one of the most important contributors to the high extent of cooperativity manifested by proteins in their cohesive domain motions. The orientations between neighboring non-bonded residues in proteins substantially follow the similar geometric regularities, regardless of whether the residues are on the surface or buried -a direct result of hydrophobicity forces. These orientations are relatively fixed and correspond cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 92 publications
1
28
0
Order By: Relevance
“…The Pearson correlation coefficient R follows the same trend. We note, that even though smaller, the correlation coefficients for rate vs. MSF are significant, which agrees with previous findings [14,32,13,15]. However, partial correlations (pR) show that once stress (MLmS) is controlled for, the rate-MSF correlation almost disappears: the sequence-flexibility correlation is indirect.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The Pearson correlation coefficient R follows the same trend. We note, that even though smaller, the correlation coefficients for rate vs. MSF are significant, which agrees with previous findings [14,32,13,15]. However, partial correlations (pR) show that once stress (MLmS) is controlled for, the rate-MSF correlation almost disappears: the sequence-flexibility correlation is indirect.…”
Section: Resultssupporting
confidence: 91%
“…Regarding the sequence-flexibility relationship, previous empirical correlation studies had already found that the sequence-flexibility relationship is nonlinear and either dismissed the nonlinear parts or attempted an interpretation in terms of different selection regimes [14,32,13]. We found the nonlinearity follows naturally from the Stress Model: evolutionary rates depend nonlinearly on MSF because they depend (approximately) linearly on MLmS , and MSF  ≈ 1/ MLmS .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…ENMs, in particular the anisotropic network model (ANM), a type of ENM that provides the directions of motions in addition to relative mobility, have proven useful for obtaining the dominant functional motions of proteins in many studies (Bahar and Rader 2005;Ma 2005;Zheng and Brooks 2005;Sen et al 2006;Tama and Brooks 2006;Jernigan and Kloczkowski 2007;Yang et al 2007Yang et al , 2008. It has been shown that the motions computed using ENMs correspond well to the principal components of molecular dynamics (MD) trajectories (Hayward and de Groot 2008), can aid in molecular structure determination (Wu and Ma 2004), refining of structural models (Delarue and Dumas 2004), and in flexible docking (May and Zacharias 2008;Gerek and Ozkan 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Further facilitating evolution in IDPs is their large fraction of solvent exposed residues; surface residues are generally subject to more frequent substitution than amino acids in the buried protein core [141]. Indeed, sequence variability correlates with protein packing density [142], implying that loosely packed proteins evolve more rapidly than proteins with high tertiary structural content. By comparing genetic distance in protein families, proteins having sizable disordered regions were found to In only two cases did disordered proteins evolve more slowly than their ordered counterparts.…”
Section: Structural Disorder and Evolutionmentioning
confidence: 99%